Exploration of Environmental Care Attitudes through Integrated Natural Science Learning with Local Potency - Azhary, Shobhi Al-Ghifari; Sumarni, Woro; Wiyanto, Wiyanto; Sarwi, Sarwi; Hartono, Hartono; Subali, Bambang (Proceedings of International Conference on Science, Education, and Technology, 2024)
This research is article review research aimed at exploring integrated natural science learning research with the local potency to improve students' environmental care attitudes published in journal articles and proceedings for 2010-2021 and categorized based on research year, research location, research institution, and subject school level. This study uses a literature review with 63 articles. The results showed that a lot of research took place in 2020 with 10 articles, mostly conducted in Indonesia with 56 articles, researched mostly by College Institution institutions with as many as 27 authors, and mostly carried out at the junior high school level with 32 articles. This article’s review shows that research on local potency to improve environmental care attitudes is still lacking and needs to be investigated further.